2014
DOI: 10.1074/jbc.m114.599712
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Causes Inflammatory Pain via Biased Agonism of PAR2 and TRPV4

Abstract: Background: Proteases trigger inflammation and pain by cleaving protease-activated receptors (PARs) at defined sites. Results: Cathepsin S (Cat-S) cleaved PAR 2 at a unique site E 56 2T 57 , leading to G␣s-mediated cAMP accumulation and TRPV4-dependent inflammation and pain. Conclusion: Cat-S is a biased agonist of PAR 2 -and TRPV4-dependent inflammation and pain. Significance: PARs integrate responses to diverse proteases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 66 publications
5
108
1
3
Order By: Relevance
“…Other proteases, including cathepsin S and elastase, are biased agonists that cleave PAR 2 at distinct sites to induce coupling to G␣ s but not G␣ q or ␤-arrestins (23)(24)(25). Cathepsin S-and elastase-activated PAR 2 cannot be reactivated by proteolysis, but the cleaved receptors remain at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other proteases, including cathepsin S and elastase, are biased agonists that cleave PAR 2 at distinct sites to induce coupling to G␣ s but not G␣ q or ␤-arrestins (23)(24)(25). Cathepsin S-and elastase-activated PAR 2 cannot be reactivated by proteolysis, but the cleaved receptors remain at the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Perforated patch clamp recording were made from small diameter neurons (Ͻ30 picofarad capacitance). Changes in excitability were quantified by measuring rheobase and number of action potential discharges at twice rheobase, as described (23). Cells were incubated for 10 min with trypsin (50 nM) or vehicle (control) and were then transferred to F-12 medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed no effects on temperature sensation, normal acute responses to noxious heat but impaired inflammatory thermal hyperalgesia while others showed deficits in acute heat responses yet no differences in behavior after inflammation (Liedtke and Friedman 2003; Suzuki and others 2003; Todaka and others 2004; Lee and others 2005; Huang and others 2011). Additionally, inflammatory mediators such as PGE 2 and PAR 2 have been shown to sensitize TRPV4 (Alessandri-Haber and others 2005; Grant and others 2007; Zhao and others 2014). These results indicate that TRPV4 could be required for normal nociception and could have a role in abnormal pain conditions.…”
Section: Trpv4mentioning
confidence: 99%